2000
DOI: 10.1074/jbc.275.1.439
|View full text |Cite
|
Sign up to set email alerts
|

Histone H2B Phosphorylation in Mammalian Apoptotic Cells

Abstract: Histone phosphorylation was investigated in several mammalian cells undergoing apoptosis (human HL-60 and HeLa, mouse FM3A and N18 cells, and rat thymocytes). Among the four nucleosomal core histones (H2A, H2B, H3, and H4), H2B, which is not usually phosphorylated in quiescent or growing cells, was found to be phosphorylated after treatment with various apoptotic inducers. The H2B was phosphorylated around the time when nucleosomal DNA fragmentation was initiated and, like this fragmentation, was completely bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 46 publications
2
76
0
1
Order By: Relevance
“…3a). Previous studies have shown that histone H2B is specifically phosphorylated during apoptosis in intact cells [24,25], however it is unknown if Ca 2+ treatment of isolated nuclei can also promote this apoptoticspecific phosphorylation of H2B. Figure 3b shows that H2B is phosphorylated in thymocytes induced to undergo apoptosis by dexamethasone, whereas H2B in isolated nuclei treated with 1 mM Ca 2+ was not phosphorylated, despite the occurrence of degraded DNA.…”
Section: Ca 2+ Induces Dna Degradation and Histone Release In Isolatementioning
confidence: 85%
See 1 more Smart Citation
“…3a). Previous studies have shown that histone H2B is specifically phosphorylated during apoptosis in intact cells [24,25], however it is unknown if Ca 2+ treatment of isolated nuclei can also promote this apoptoticspecific phosphorylation of H2B. Figure 3b shows that H2B is phosphorylated in thymocytes induced to undergo apoptosis by dexamethasone, whereas H2B in isolated nuclei treated with 1 mM Ca 2+ was not phosphorylated, despite the occurrence of degraded DNA.…”
Section: Ca 2+ Induces Dna Degradation and Histone Release In Isolatementioning
confidence: 85%
“…During analysis of histone H2B phosphorylation, thymocytes were treated with 1 μM dexamethasone for 4 h and nuclei were incubated with CaCl 2 and harvested. Histones were extracted [24] and western blotted against anti-phospho S14H2B (Upstate) [25].…”
Section: Sds Gel Electrophoresis and Western Blottingmentioning
confidence: 99%
“…An appealing hypothesis could be that anti-lamin Abs are generated as a secondary response to apoptotic cells, exhibiting phosphorylated cleaved lamins [41,42]. Such a response to phosphorylated nucleoproteins in apoptotic cells as well as defects in the clearing of these apoptotic cells are often advocated in the recent models of autoimmunity [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Histone phosphorylation has been linked to diverse biological functions, including chromosome condensation (H1 and H3 phosphorylation; reviewed in [162,163]), transcriptional regulation (H3 phosphorylation; reviewed in [164,165]), DNA damage repair (H2A.X phosphorylation; [97,166,167]), and even apoptosis (H2B phosphorylation; [168][169][170][171]). Phosphorylation adds negative charges to the modified protein, and similar to histone acetylation, phosphorylation can decrease the association of the modified histones with DNA.…”
Section: Histone Phosphorylationmentioning
confidence: 99%